Social network of producers of dehydrated products with thermosolar technology in Zacatecas, Mexico (Agro Productividad, 2024)
Objective: To analyze the social networks and the trust there is among the producers of dehydrated productswith thermosolar technology in the agricultural strip of Zacatecas, in order to determine the organizationalpotential through prevailing levels of trust between producers.Design/methodology/approach: A survey was applied to 30 producers of dehydrated products who havereceived training and information about the use of the thermosolar plant, all belonging to the state of Zacatecas.Indicators were used for the social networks analysis.Results: The results confirmed the importance of direct and indirect links; of all the producers, eighteenhad no relationship with any other producer, although the rest showed at least one interaction with anotherproducer. The producers have notable characteristics and acceptable trust relationships.Limitations on study/implications: The results apply to the selected sample; thermosolar food dehydrationtechnology is still unknown among the producers.Findings/conclusions: Trust relationships must be strengthened and strategies should be created to disseminateknowledge in a timely and efficient manner with key stakeholders and thus boost their pre-existing interactions.